Valorisation of brazilian pine-fruit shell residue (araucaria angustifolia) in the production of biopolyols - Rezende, Stephany (2017)
The valorisation of agro-forestry residues, namely the ones which do not have commercial value, have attracted the interest of academia and industrials contributing to generate new alternatives in the eld of chemicals and materials. The purpose is not only promoting their reuse to generate value- added products, but also highlight the production of bio-based products from renewable resources. Araucaria angustifolia is a coniferous tree native of South America, found in the South and Southwest of Brazil, part of a whole vegetation of the Atlantic Forest. The Brazilian pine-fruit shell (PFS) is an attractive lignocellulosic residue with potential to be used as a raw material to produce polymeric materials. In this context, this work comprises the characterization of PFS and their use to produce polyols trough oxypropylation